A Case of Multiple Endocrine Neoplasia Type 1 Combined with Papillary Thyroid Carcinoma - Kim, Hai-Jin (Yonsei University College of Medicine, 2008)
This is the first report of papillary thyroid carcinoma combined with multiple endocrine neoplasia type 1 (MEN1) in Korea. MEN1 is a hereditary disease comprising neoplastic disorders such as pituitary, parathyroid and pancreatic neuroendocrine tumor, such as gastrinoma. But papillary thyroid cancer was never regarded as its component before in Korea. Herein we present a 39-year-old woman who manifested typical features of MEN1 with a coincidental papillary thyroid carcinoma. Although the family history of MEN1 was definite, her genetic analysis of DNA had revealed no germline mutation in MEN1 gene locus. Unidentified culprit gene unable us further genetic study to find LOH (loss of heterogeneity) in 11q13, the possible explanation of papillary thyroid carcinoma as a new component of MEN1. As we have first experienced a case of MEN1 combined with papillary thyroid carcinoma in Korea, we report it with the review of literature.